Between church and state, confession and science on the position of theological faculties at German universities. Issue 3 (2nd October 2021) - Schmidt, Jochen
ABSTRACT: Christian Theology at the German university falls between two stools in many ways: Theology is an academic discipline and participates in the freedom of science; at the same time, theology is linked to the church by laws between the churches and the Federal States; furthermore, theology serves to train school teachers and/or ministers, though it also contributes to the life of the university in conjunction with other disciplines and fields of study. Looking at the field of church history in particular, this paper argues that the tensions that theology finds itself in are productive tensions and that the disputes that surround the complex situation of theology – faculties of theology in particular – at the German university can provoke theology to ponder on the balance between its commitment to the Christian faith on the one hand and to uncompromising academic rigour on the other hand.